2002
DOI: 10.1080/14634980290031866
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal distribution in bottom sediments of a Mexican reservoir

Abstract: Sediments from the Jose Antonio Alzate Reservoir (México) that receives large amount of industrial and municipal untreated waste water were analyzed in order to explore pollution by heavy metals. Samples from ten locations were analyzed to obtain particle size and concentrations of selected heavy metals in different sieve size fractions. Areas of deposition of fines are illustrated. The analysis of metal concentration by size fraction, the relative presence of metals, the ratio of metal concentrations to sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Without presenting the full correlation and regression A geochemical and statistical approach for assessing heavy metal... results, it should be noted that when the six metals were correlated with the different grain size fractions it was observed that the grain size of the sediments did not have a noticeable pronounced effect on the spatial distribution of heavy metals. One reason for this occurrence could be the fact that the analyzed grain sizes were not in the very fine material range (< 0.063 mm) which numerous investigators (for example, Förstner, et al,1982;Cauwet, 1987;Arujo, et al, 1988;Chakrapani and Subramanian, 1993;Maurer, et al, 1994;De Gregori, et al, 1996;Ujevi, et al, 2000;Zhang, et al, 2001;Avila-Perez, et al, 2002;Che, et al, 2003) found to be associated with the highest concentrations of heavy metals. In addition to correlation and regression analysis, discriminant analysis was used to investigate whether the spatial variations of the various metals along the coast had statistically significant concentrations in specific (i.e., localized) or well-defined geographic areas.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Without presenting the full correlation and regression A geochemical and statistical approach for assessing heavy metal... results, it should be noted that when the six metals were correlated with the different grain size fractions it was observed that the grain size of the sediments did not have a noticeable pronounced effect on the spatial distribution of heavy metals. One reason for this occurrence could be the fact that the analyzed grain sizes were not in the very fine material range (< 0.063 mm) which numerous investigators (for example, Förstner, et al,1982;Cauwet, 1987;Arujo, et al, 1988;Chakrapani and Subramanian, 1993;Maurer, et al, 1994;De Gregori, et al, 1996;Ujevi, et al, 2000;Zhang, et al, 2001;Avila-Perez, et al, 2002;Che, et al, 2003) found to be associated with the highest concentrations of heavy metals. In addition to correlation and regression analysis, discriminant analysis was used to investigate whether the spatial variations of the various metals along the coast had statistically significant concentrations in specific (i.e., localized) or well-defined geographic areas.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Without presenting the full correlation and regression results, it should be noted that when the six metals were correlated with the different grain size fractions it was observed that the grain size of the sediments did not have a noticeable pronounced effect on the spatial distribution of heavy metals. One reason for this occurrence could be the fact that the analyzed grain sizes were not in the fine material range (<0.063 mm), which numerous investigators (for example, Förstner et al, 1982;Cauwet, 1987;Arujo et al, 1988;Chakrapani and Subramanian, 1993;Maurer et al, 1994;De Gregori et al, 1996;Ujevi et al, 2000;Zhang et al, 2001;Avila-Perez et al, 2002;Che et al, 2003) found to be associated with the highest concentrations of heavy metals.…”
Section: Statistical Analysesmentioning
confidence: 91%
“…In the last years, a larger number of environmental studies were started on Lerma River (Avila-Pérez et al [3], Barceló et al [4], Mantilla-Morales et al [5]), in order to better know the conditions and suggest potential solutions. The last studies were interested not only in the conventional parameters (BOD, DO, Solids, etc.)…”
Section: Introductionmentioning
confidence: 99%